Dilemmatic Challenges of Budgeting for Poverty in Local Government in Indonesia - Maulana, Bonnix Hedy; Wijayanti, Sukma (Yayasan Sinergi Kawula Muda, 2023)
This study aims to identify risk conditions in budgeting inhibiting Local Government when ensuring pro-poor budgeting each year. Qualitative was used in this study, and Semi-structured interviews were conducted with senior managers and local government staff involved with managing pro-poor budgeting. The main findings, first, is the dilemma in determining budgeting priorities in the region, then at the end of the budgeting process in the budget battle that is raised in the expectations. The emerging political risks evolve from maximizing interests by realizing political promises as a form of moral accountability